Phenolic compounds affect production of pyocyanin, swarming motility and biofilm formation of Pseudomonas aeruginosa - KARAHASAN, AYŞEGÜL; TINAZ, GÜLGÜN; AKSU, MEHMET BURAK (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2016)
Objective: To investigate the effects of plant-derived phenolic compounds (i.e. caffeic acid, cinnamic acid, ferulic acid and vanillic acid) on the production of quorum sensing regulated virulence factors such as pyocyanin, biofilm formation and swarming motility of Pseudomonas aeruginosa (P. aeruginosa) isolates. Methods: Fourteen clinical P. aeruginosa isolates obtained from urine samples and P. aeruginosa PA01 strain were included in the study. The antibacterial effects of phenolic compounds were screened by well diffusion assay. Pyocyanin and biofilm activity were measured from culture supernatants and the absorbance values were measured using a spectrophotometer. Swarming plates supplemented with phenolic acids were point inoculated with P. aeruginosa strains and the ability to swarm was determined by measuring the distance of swarming from the central inoculation site. Results: Tested phenolic compounds reduced the production of pyocyanin and biofilm formation without affecting growth compared to untreated cultures. Moreover, these compounds blocked about 50% of biofilm production and swarming motility in P. aeruginosa isolates. Conclusions: We may suggest that if swarming and consecutive biofilm formation could be inhibited by the natural products as shown in our study, the bacteria could not attach to the surfaces and produce chronic infections. Antimicrobials and natural products could be combined and the dosage of antimicrobials could be reduced to overcome antimicrobial resistance and drug side effects.
Keywords: QUORUM SENSING INHIBITION; PHYTOCHEMICALS; PLANT